2013
DOI: 10.1037/a0032776
|View full text |Cite|
|
Sign up to set email alerts
|

Noradrenergic alpha-2 receptor modulators in the ventral bed nucleus of the stria terminalis: Effects on anxiety behavior in postpartum and virgin female rats.

Abstract: Emotional hyper-reactivity can inhibit maternal responsiveness in female rats and other animals. Maternal behavior in postpartum rats is disrupted by increasing norepinephrine release in the ventral bed nucleus of the stria terminalis (BSTv) with the α2-autoreceptor antagonist, yohimbine, or the more selective α2-autoreceptor antagonist, idazoxan (Smith et al., 2012). Because high noradrenergic activity in the BSTv can also increase anxiety-related behaviors, increased anxiety may underlie the disrupted mother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 142 publications
(232 reference statements)
1
21
0
Order By: Relevance
“…The BSTv contains the densest noradrenergic plexus in the forebrain (Kilts and Anderson, 1986; Fendt et al, 2005) and is intimately associated with anxiety in mammals (Davis et al, 2010). Although we have found that acute suppression or stimulation of norepinephrine release in the BSTv has little effect on anxiety-related behavior in randomly selected postpartum female rats (Smith et al, 2013), longer term manipulation of noradrenergic activity in the BSTv (hours or days rather than minutes) could be found to have consequences for their anxiety (Choi et al, 2008). In addition to affecting the BSTv, high brainstem DBH synthesis in low-anxiety mothers while they interact with pups could be associated with activation of forebrain-projecting noradrenergic cells of the locus coeruleus that increase maternal arousal and attention to external sensory information (Aston-Jones et al, 1999; Berridge and Waterhouse, 2003) or even brainstem adrenergic cells that influence autonomic function (Madden and Sved, 2003).…”
Section: Discussionmentioning
confidence: 77%
“…The BSTv contains the densest noradrenergic plexus in the forebrain (Kilts and Anderson, 1986; Fendt et al, 2005) and is intimately associated with anxiety in mammals (Davis et al, 2010). Although we have found that acute suppression or stimulation of norepinephrine release in the BSTv has little effect on anxiety-related behavior in randomly selected postpartum female rats (Smith et al, 2013), longer term manipulation of noradrenergic activity in the BSTv (hours or days rather than minutes) could be found to have consequences for their anxiety (Choi et al, 2008). In addition to affecting the BSTv, high brainstem DBH synthesis in low-anxiety mothers while they interact with pups could be associated with activation of forebrain-projecting noradrenergic cells of the locus coeruleus that increase maternal arousal and attention to external sensory information (Aston-Jones et al, 1999; Berridge and Waterhouse, 2003) or even brainstem adrenergic cells that influence autonomic function (Madden and Sved, 2003).…”
Section: Discussionmentioning
confidence: 77%
“…Subjects were female Long-Evans rats born and raised in our breeding colony and maintained as previously described (Smith et al, 2013). Pregnant females were singly housed approximately five days before parturition, and litters culled to contain four males and four females within 24 hours after birth.…”
Section: Methodsmentioning
confidence: 99%
“…Lonstein 24 in the mPFC was positively associated with retrieval in nulliparae, but negatively associated with the frequency of licking in the postpartum females. Differences between the female reproductive states in basal mPFC serotonergic activity may help explain the opposite directions of effects, because dams already have higher serotonin metabolism in the cortex and some other brain sites compared to virgins or pregnant females (e.g., Desan et al, 1988;Lonstein, Dominguez, Putnam, Vries, and Hull, 2003;Smith, Piasecki, Weera, Olszewicz, and Lonstein, 2013), so perhaps serotonergic activity in the mPFC that is neither too high nor too low is optimal for maternal responsiveness -lower levels in dams but higher levels in virgins meet in the middle to promote maternal responsiveness in both groups. It should also be recognized that while sensitized and postpartum maternal behaviors appear quite similar, the behaviors do not necessarily emerge via similar neurochemical processes.…”
Section: Accepted Manuscriptmentioning
confidence: 97%